2009
DOI: 10.1097/dmp.0b013e3181b65895
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Work Injuries Involving Natural Disasters, 1992–2006

Abstract: Despite an increasing social emphasis on disaster preparation and response, there has been little increase in expert knowledge about how people actually perish in these large-scale events. Using a 2-way classification structure, this study identifies areas of emphasis in preventing occupational deaths from various natural disasters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 10 publications
0
36
0
Order By: Relevance
“…Many occupational fatalities have occurred during post-storm clean-up and reconstruction. One study found that, at median, occupational deaths occurred 36.5 days after a storm event [7] and were most often associated with clean-up (44%), restorative construction (26%), public utilities restoration (8%), and security/policing (6%). Residents and volunteers trying to clean affected homes could suffer non-fatal injuries (including cuts, wounds, sprains, and strains) and other health risks during the course of removing debris or during minor and major home repairs (for instance, removing wet building materials or wet wall insulation).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many occupational fatalities have occurred during post-storm clean-up and reconstruction. One study found that, at median, occupational deaths occurred 36.5 days after a storm event [7] and were most often associated with clean-up (44%), restorative construction (26%), public utilities restoration (8%), and security/policing (6%). Residents and volunteers trying to clean affected homes could suffer non-fatal injuries (including cuts, wounds, sprains, and strains) and other health risks during the course of removing debris or during minor and major home repairs (for instance, removing wet building materials or wet wall insulation).…”
Section: Resultsmentioning
confidence: 99%
“…Large-scale displacement could increase demands on the transportation infrastructure, and there may be occupational health concerns for municipal workers deployed to address flooding in transportation and communications infrastructure [7]. …”
Section: Resultsmentioning
confidence: 99%
“…Wildfires (80), hurricanes (72), and floods (62) accounted for most of these occupational weather-related fatalities [45] . Fatal injuries were associated with different phases of the response for each of these disaster types.…”
Section: Occupational Health Hazards and Effects Related To Climate Cmentioning
confidence: 99%
“…For wildland fires, 80% of the 80 deaths affected workers who were attempting to put out or divert the fires, whereas for hurricanes, more than 60% of the 72 deaths occurred after the disaster event and affected workers involved in clean up, restorative construction, and restoration of public utilities. For flooding events, 45% of all 62 workers who died were operating or riding in a motor vehicle at the time of the injury [45] . Models predict lightning strikes in the United States to increase 12 ± 5% per degree Celsius and occur at about 50% greater frequency over the 21st century [63] .…”
Section: Occupational Health Hazards and Effects Related To Climate Cmentioning
confidence: 99%
“…These typically workrelated deaths occur up to 37 days after landfall of the storm (Fayard 2009) and lead to an increase in the number of calls to Poison Control Centers (Forrester 2009). Recent studies also suggest that storms may influence the mortality rate through other less observable mechanisms (Combs et al 1996;Hendrickson and Vogt 1996;Jonkman and Kelman 2005).…”
Section: Introductionmentioning
confidence: 99%